2019
DOI: 10.1038/s41598-018-37405-w
|View full text |Cite
|
Sign up to set email alerts
|

Limbic control over the homeostatic need for sodium

Abstract: The homeostatic need for sodium is one of the strongest motivational drives known in animals. Although the brain regions involved in the sensory detection of sodium levels have been mapped relatively well, data about the neural basis of the motivational properties of salt appetite, including a role for midbrain dopamine cells, have been inconclusive. Here, we employed a combination of fiber photometry, behavioral pharmacology and c-Fos immunohistochemistry to study the involvement of the mesocorticolimbic dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…More recently, Verharen, et al (2019), using a long pause criterion to define episodes of licking (see above), reported a general trend towards sodium depletion increasing cluster number and cluster size. Moreover, sodium depletion also appeared to increase water intake during the same consumption test, but this later effect was only driven by an increase in the number of clusters and not cluster size.…”
Section: Effect Of Sodium Depletion On Lick Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Verharen, et al (2019), using a long pause criterion to define episodes of licking (see above), reported a general trend towards sodium depletion increasing cluster number and cluster size. Moreover, sodium depletion also appeared to increase water intake during the same consumption test, but this later effect was only driven by an increase in the number of clusters and not cluster size.…”
Section: Effect Of Sodium Depletion On Lick Microstructurementioning
confidence: 99%
“…The study by Verharen, et al (2019), discussed in the above section, is a notable exception as they studied water intake in rats with and without 7-h water restriction. Water restriction was observed to increase the number of drinking bouts without affecting their size, although it should be noted that the analysis parameters used here differed from those conventionally used in lick microstructure studies.…”
Section: Effect Of Water Depletion and Thirst On Lick Microstructurementioning
confidence: 99%
“…Sections (approximately + 1.5 mm Bregma for VS and + 3.7-4.2 mm Bregma for vmPFC) were photographed using a brightfield microscope (at a × 5 magnification; AxioImager M2), and c-Fos analysis was performed in a semi-automated fashion using an ImageJ (Version 1.51s) routine (Verharen et al 2019a). First, the microscopic images were Fouriertransformed, and a band-pass filter was applied, band-pass filtering structures of approximately the size of c-Fos-expressing nuclei (filter was set between 3 and 6 pixels).…”
Section: C-fos Immunohistochemistrymentioning
confidence: 99%
“…For instance, the activity of dopaminergic neurons in the VTA, which is thought to exhibit a robust relationship with the RL process in the brain ( Nakanishi et al, 2014 ; Schultz, 2015 ), increases when sodium-depleted mice lick saltwater. In contrast, pharmacological inactivation of neural projections from the VTA to the nucleus accumbens decreases sodium intake ( Verharen et al, 2019 ). In addition, recent studies have indicated that optogenetic excitation of VTA dopaminergic neurons suppresses sodium intake in sodium-depleted mice ( Sandhu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of dopaminergic neurons in the ventral tegmental area (VTA), which exhibit robust correlations with reward systems, decreases salt intake ( Sandhu et al, 2018 ). Recent evidence also indicates that dopaminergic neurons in the midbrain may encode appetitive properties of sodium ( Verharen et al, 2019 ) and reward prediction error ( Cone et al, 2016 ), while some excitatory neurons in the pre-locus coeruleus decrease sodium appetite ( Lee et al, 2019 ). Conversely, the activation of neurons in the subfornical organ has been shown to increase sodium appetite ( Matsuda et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%